RAD-Deficient Human Cardiomyocytes Develop Hypertrophic Cardiomyopathy Phenotypes Due to Calcium Dysregulation - Li, Ya’nan; Chang, Yun; Li, Xiaolei; Li, Xiaowei; Gao, Jian; Zhou, Yafei; Wu, Fujian; Bai, Rui; Dong, Tao; Ma, Shuhong; Zhang, Siyao; Lu, Wen-Jing; et al. (Frontiers in Cell and Developmental Biology, 2020)
Ras associated with diabetes (RAD) is a membrane protein that acts as a calcium channel regulator by interacting with cardiac L-type Ca2 + channels (LTCC). RAD defects can disrupt intracellular calcium dynamics and lead to cardiac hypertrophy. However, due to the lack of reliable human disease models, the pathological mechanism of RAD deficiency leading to cardiac hypertrophy is not well understood. In this study, we created a RRAD–/– H9 cell line using CRISPR/Cas9 technology. RAD disruption did not affect the ability and efficiency of cardiomyocytes differentiation. However, RAD deficient hESC-CMs recapitulate hypertrophic phenotype in vitro. Further studies have shown that elevated intracellular calcium level and abnormal calcium regulation are the core mechanisms by which RAD deficiency leads to cardiac hypertrophy. More importantly, management of calcium dysregulation has been found to be an effective way to prevent the development of cardiac hypertrophy in vitro.